2019
DOI: 10.3390/nu11112830
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to the Mediterranean Diet and Its Association with Body Composition and Physical Fitness in Spanish University Students

Abstract: The aims of this study were to assess the association of adherence to the Mediterranean diet (MD) with physical fitness and body composition in Spanish university students and to determine the ability to predict the MD adherence of each Mediterranean Diet Adherence Screener (MEDAS) item. A cross-sectional study was performed involving 310 first-year university students. Adherence to the MD was evaluated with MEDAS-14 items. Anthropometric variables, body composition, and physical fitness were assessed. Muscle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
58
4
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(88 citation statements)
references
References 64 publications
22
58
4
4
Order By: Relevance
“…Compared with other studies, university students in this study had higher adherence to the Mediterranean diet than other investigations carried out among university students in Castilla-La Mancha [ 27 , 28 , 29 ], which ranged from 5 to 9%. University students from Navarra also showed less adherence [ 30 ] as did studies from other countries, such as Cyprus [ 31 ], Turkey [ 32 ], and Tunisia [ 33 ].…”
Section: Discussioncontrasting
confidence: 83%
“…Compared with other studies, university students in this study had higher adherence to the Mediterranean diet than other investigations carried out among university students in Castilla-La Mancha [ 27 , 28 , 29 ], which ranged from 5 to 9%. University students from Navarra also showed less adherence [ 30 ] as did studies from other countries, such as Cyprus [ 31 ], Turkey [ 32 ], and Tunisia [ 33 ].…”
Section: Discussioncontrasting
confidence: 83%
“…Our proportion of low adherence to the MD was slightly lower than the percentage reported in women in two previous recent studies on university students in central Spain, which identified adherence rates as low as 20% and 38.1% for this type of diet [ 32 , 33 ]. Regarding the rates for women with high adherence to the MD, they were higher than those identified in previous studies such as that of García-Meseguer et al who identified a high adherence in only 6.9% of women [ 33 ].…”
Section: Discussioncontrasting
confidence: 83%
“…Previous work found in adolescents that a "fruit and vegetables" dietary pattern was positively associated with VO 2max [16]. In a recent study conducted in university students, the authors observed that a high level of adherence to the MedD was associated with a high level of CRF, although the prevalence of high adherence to MedD was low [22]. They found MedD scores of 7.2 ± 1.9 points in men and 6.9 ± 2 points in women, slightly higher than ours; 6.2 in both sexes.…”
Section: Discussionmentioning
confidence: 93%